RPE and Velocity Relationships for the Back Squat, Bench Press, and Deadlift in Powerlifters. Issue 2 (February 2017) - Helms, Eric R.; Storey, Adam; Cross, Matt R.; Brown, Scott R.; Lenetsky, Seth; Ramsay, Hamish; Dillen, Carolina; Zourdos, Michael C.
Abstract: Helms, ER, Storey, A, Cross, MR, Browm, SR, Lenetsky, S, Ramsay, H, Dillen, C, and Zourdos, MC. RPE and velocity relationships for the back squat, bench press, and deadlift in powerlifters. J Strength Cond Res 31(2): 292–297, 2017—The purpose of this study was to compare average concentric velocity (ACV) and rating of perceived exertion (RPE) based on repetitions in reserve on the squat, bench press, and deadlift. Fifteen powerlifters (3 women and 12 men, mean age 28.4 ± 8.5 years) worked up to a one repetition maximum (1RM) on each lift. Rating of perceived exertion was recorded on all sets, and the ACV was recorded for all sets performed at 80% of estimated 1RM and higher, up to 1RM. Rating of perceived exertion at 1RM on squat, bench press, and deadlift was 9.6 ± 0.5, 9.7 ± 0.4, and 9.6 ± 0.5, respectively and was not significantly different ( p > 0.05). The ACV at 1RM on squat, bench press and deadlift was 0.23 ± 0.05, 0.10 ± 0.04, and 0.14 ± 0.05 m·second −1, respectively. Squat was faster than both bench press and deadlift ( p > 0.001), and deadlift was faster than bench press ( p = 0.05). Very strong relationships ( r = 0.88–0.91) between percentage 1RM and RPE were observed on each lift. The ACV showed strong ( r = −0.79 to −0.87) and very strong ( r = −0.90 to 92) inverse relationships with RPE and percentage 1RM on each lift, respectively. We conclude that RPE may be a useful tool for prescribing intensity for squat, bench press, and deadlift in powerlifters, in addition to traditional methods such as percentage of 1RM. Despite high correlations between percentage 1RM and ACV, a "velocity load profile" should be developed to prescribe intensity on an individual basis with appropriate accuracy.